A quantitative exploration of traditional medicinal plants of Koh Valley Chitral, Hindukush Range, Pakistan - Fazal, Zahid; Badshah, Lal; Khan, Muhammad Nauman; Kaplan, Alevcan; Ali, Amjad; Husssain, Wahid (Ethnobotany Research and Applications, 2024)
Background: This is the first quantitative study on the traditional use of important medicinal plants in Koh Valley Chitral, Hindukush range, Pakistan. This research explores the relationship between local communities and medicinal plants in their daily lives and provides practical knowledge for maintaining health. Methods: A total of 160 informants were interviewed, including inhabitants of the study area of both genders and traditional healers. Visual assessment and rural appraisal methods were used together with semi-structured interviews and open-ended questionnaires. The data collected were analyzed quantitatively using the following parameters: Frequency of citation, relative frequency of citation, reports on the importance of using to family, parts used and their use. Results: The ethnomedicinal study revealed that a total of 128 plant species belonging to 104 genera and 51 families were reported. The study showed that Asteraceae was the dominant family with 14 species. The life form showed that herbs were the leading group (82 species), while fruits (42 species), were the most commonly used plant parts. Berberis lycium is the most commonly medicinal plant in this area. Other plants were also used for the treatment of different diseases. Fifty two (52 species), are commonly used for diseases of the gastrointestinal tract. The RFC values ranges from 0.05 to 0.29. Asteraceae showed the highest FIV value (183.13), followed by Rosaceae (180.6). Papaver somniferum has the highest usage report (UR-16), indicates that, in a specific ethnobotanical study, this plant was cited for the most diverse applications among all the plants documented. Conclusions: The identified plants showed strong therapeutic properties and this research will be the basic guideline for the preservation of ethnomedicinal knowledge, heritage and crude drug practices in the context of the development of new herbal medicines. Keywords: Traditional Knowledge; Importance value; RFC; Use report; Koh Valley